HUBUNGAN DUKUNGAN SUAMI DENGAN PEMILIHAN TEMPAT PERSALINAN PADA IBU HAMIL DI DESA PENFUI TIMUR - Odi L. Namangdjabar; Matje Meriaty Huru (Jurnal Medicare, 2026)
Choosing a place of delivery is an important effort to reduce the Maternal Mortality Rate (MMR). Husband's support plays a role in influencing pregnant women's decisions to choose a safe birthing place in a health facility. This study aims to determine the relationship between husband's support and the choice of place of delivery for pregnant women in the third trimester in East Penfui Village . This research uses an observational analytic design with a cross-sectional approach. The research sample consisted of 101 pregnant women in the third trimester who were selected using a total sampling technique. Data were collected through a structured questionnaire and analyzed univariately and bivariately using the Chi-Square test with a significance level of α = 0.05. The research results showed that the majority of respondents received good husband support (76.2%) and chose a health facility as a place to give birth (97.0%). Bivariate analysis shows that mothers who received good husband support mostly chose health facilities as the place of delivery (76.2%). The results of the Chi-Square test show a value of p = 0.012 (p < 0.05), which means there is a significant relationship between husband's support and the choice of place of delivery for third trimester pregnant women in East Penfui Village.